Effect of total flavonoids of Spatholobus suberectus Dunn on PCV2 induced oxidative stress in RAW264.7 cells - Hai-lan Chen; Jian Yang; Yuan-fang Fu; Xi-nan Meng; Wei-dan Zhao; Ting-jun Hu (BMC, 2017)
Abstract Background This study was carried out to investigate the effect of total flavonoids of Spatholobus suberectus Dunn (TFSD) on PCV2 induced oxidative stress in RAW264.7 cells. Methods Oxidative stress model was established in RAW264.7 cells by infecting with PCV2. Virus infected cells were then treated with various concentrations (25 mg/ml, 50 mg/ml and 100 mg/ml) of TFSD. The levels of oxidative stress related molecules (NO, ROS, GSH and GSSG) and activities of associated enzymes (SOD, MPO and XOD were analyzed using ultraviolet spectrophotometry, fluorescence method and commercialized detection kits. Results PCV2 infection induced significant increase of NO secretion, ROS generation, GSSG content, activities of both XOD and MPO, and dramatically decrease of GSH content and SOD activity in RAW264.7 cells (P < 0.05). After treating with TFSD, PCV2 induced alteration of oxidative stress related molecule levels and enzyme activities were recovered to a level similar to control. Conclusion Our findings indicated that TFSD was able to regulate oxidative stress induced by PCV2 infection in RAW264.7 cells, which supports the ethnomedicinal use of this herb as an alternative or complementary therapeutic drug for reactive oxygen-associated pathologies.